Analysis of the financial condition of the enterprise - Vidrya, E. V.; Pererva, P. G. (My University, 2023)
It is well-founded that the financial condition of an industrial enterprise determines the competitiveness of the enterprise, its potential in business cooperation, assesses the extent to which the economic interests of the enterprise itself and its partners are secured in financial and other relations.
Аналіз фінансового стану підприємства
Keywords: financial analysis; economics; management; research; monitoring; enterprises